Changes in diet and coronary heart disease mortality among social classes in Great Britain. Issue 2 (June 1989) - Morgan, M; Heller, R F; Swerdlow, A
Abstract : Coronary heart disease (CHD) mortality has declined in Britain since the early 1970s and followed a reduction in dietary fat intake in the population. We attempted to determine whether there have been changes in dietary fat intakes by social classes and to see whether they correspond to social class changes in CHD mortality, where the greatest reduction has been in the upper social class groups. Dietary fat intake was specially obtained by social class on a household basis from the National Food Survey (NFS) for 1974 and 1981. The decline in saturated fat intake and increase in polyunsaturated fat is shown to have occurred in each social class group, although it was not possible to examine the data separately for men and women. In contrast, the decline in the proportion of current smokers between 1974 and 1980 (from the General Household Survey) was greatest in the higher social classes. Rates of CHD mortality showed the greatest decline among men in social classes I & II over the period 1969/73 to 1979/83. However, despite some problems in the interpretation of the data collected by the NFS, this study shows that recent social class trends in dietary fat intakes are unlikely to account for the differential changes in CHD mortality. Changes in the prevalence of smoking among social classes are more consistent with the change in CHD mortality.